PENGARUH LENSA KONTAK LUNAK TERHADAP KENYAMANAN PEMAKAIAN DI SMK KESEHATAN LETRIS - Dyas Rahmawati; Wahyu Budiana; Bunyamin Rizki Abdillah (Jurnal Mata Optik, 2022)
This study aims to determine the effect of the use of soft contacts on the comfort of wearing on students of SMK Kesehatan Letris. The study was conducted using descriptive qualitative methods to determine complaints and the impact of soft contact lenses on wearing comfort. This study involved 19 respondents aged between 16 and 17 years with details of 10 respondents in the case group and 9 respondents in the control group. The results showed that 70% of users felt a sensation of dry eyes, 80% felt that their eyes felt lumpy or uncomfortable, this was related to the selection of soft contact lenses based on 80% water content. It can be concluded that soft contact lenses affect the comfort of wearing which is related to the selection of the moisture content of the contact lens material and the humidity of the room.